Promoting global monetary and financial stability : the Bank for International Settlements after Bretton Woods, 1973-2020 - Borio, C. E. V.; Claessens, Stijn; Clement, Piet; McCauley, Robert N.; Shin, Hyun Song (Cambridge : Cambridge University Press, 2020)
As the global organisation of central banks, the Bank for International Settlements (BIS) has played a significant role in the momentous changes the international monetary and financial system has undergone over the past half century. This book offers a key contribution to understanding these changes. It explores the rise of the emerging market economies, the resulting shifts in the governance of the international financial system, and the role of central bank cooperation in this process. In this truly multidisciplinary effort, scholars from the fields of economics, history, political science and law unravel the most poignant episodes that marked this period, including European monetary unification, the paradigm shifts in economic and financial analysis, the origins and influence of macro-financial stability frameworks, the rise of soft law in international financial governance, central bank crisis management in the wake of the Great Financial Crisis, and, finally, the institutional evolution of the BIS itself.
Title from publisher's bibliographic system (viewed on 22 Apr 2020).
Keywords: Bank for International Settlements; Monetary policy